A new empirical approach for rapid quantification of organic and pyritic sulfur in sedimentary rocks using the Rock-Eval 7S. (April 2022) - Cohen-Sadon, Hadar; Amrani, Alon; Feinstein, Shimon; Rosenberg, Yoav Oved
Highlights: Robust and rapid analysis of organic and pyritic sulfur concentrations. Pyrolyzed organic sulfur recovery is not affected by the rock's mineral matrix. Pyrolysis amenable organic sulfur depends on its bulk thermal stability: Tmax-S. Linear correlation between the percentage of pyrolysis organic sulfur to Tmax-S. Empirical relationship resolves the organic and pyritic sulfur concentrations. Abstract: Evaluation of individual sulfur (S) fractions in sedimentary rocks (e.g., pyrite, organic-S) provides essential information about paleo-environmental conditions of sediment deposition and petroleum systems characteristics. However, measuring organic- and pyritic-S concentrations involves tedious and time-consuming (days per sample) wet chemistry techniques. A more tractable approach uses gradual heating of the rock to separate the S-fractions according to their different thermal stabilities. Such an approach is implemented here using the newest Rock-Eval model (RE-7S, Vinci Technologies), which allows monitoring of the S products during gradual heating in sequential pyrolysis and combustion cycles. The rapid (∼1 h per sample) analysis differentiates between the peaks of pyrolyzed organic- and pyritic-S. However, the residual S of both organic and pyritic fractions is decomposed at the same temperature range during combustion, challenging their quantitative separation. Here we suggest an empirical approach to separate the S-fractions based on a linear correlation (R 2 = 0.98, n = 9) between two new defined parameters: the relative amount of pyrolyzed organic-S (PyOS %) to the temperature at maximum organic-S elution during pyrolysis cycle (Tmax-S °C). The correlation was common to nine source rocks, including Types I, II, and II-S kerogens, varied S concentrations (0.8–8.7 wt%), and different mineral matrices (carbonates, siliceous). The average precision achieved by the approach was 6% relative standard deviation for replicate measurements. Accuracy was mostly within 10% compared with the values determined by the conventional wet-chemistry technique. This new empirical approach provides a rapid and robust method for quantifying organic and pyritic sulfur in sedimentary rocks.